Srimad Bhagavad Gita-Based Affirmations for Chakra Activation: A Thematic Review - Kumkaria, Bodhraj; Tiwari, Himalaya (International Journal of Psychosocial Rehabilitation, 2029)
This theoretical review explores the thematic alignment between affirmations derived from the Srimad Bhagavad Gita (SBG) and the psychoenergetic functions of the seven chakras in Indian psychology. Drawing from spiritual philosophy, yoga psychology, and neurocognitive science, the paper presents a novel chakra activation model based on Gita shlokas reframed as affirmations. Using a theoretical thematic analysis approach, selected verses were interpreted for their symbolic resonance with the psychosomatic qualities of each chakra. The findings suggest that SBGbased affirmations can functionally fulfill the roles of traditional Bīja Mantras by combining semantic intention, vibrational rhythm, and meditative repetition. The review also examines the neuroscientific underpinnings of affirmation practices— highlighting how they modulate brain areas associated with emotional regulation, attention, and self-integration. Implications are discussed for Indian psychology, transpersonal therapy, chakra-based interventions, and spiritual well-being. This research contributes a scripturally grounded, psychologically informed model for integrative spiritual practice and future empirical exploration.